(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
Social and economic changes around the world are influencing the concept of urban development. The economic aspect has always played a decisive role in the formation of cities, which in our time have become an important factor in human life. The article explores the impact of the Smart City concept on urban economy, which has become one of the relevant phenomena of the new era and one of the sustainable urban models. The main objective of the study is to identify the relationship between the smart city and urban economy, the emerging new patterns and trends that have become a trend of modernity. The paper firstly discusses the smart city system and then explores the concept of urban economy and the impact of smart city on it. The smart city models applied around the world have also been studied and suggestions for the formation of smart city transition policies have been developed. Due to the fact that the research method of the article is theoretical and methodological in nature, the obtained conclusions are explicative in character. Keywords: Smart City, Urban Economy, digitalisation, Data driven, Sustainable development, Digital Citizen, digital innovations